Penerapan Sequential Pattern Mining pada Data Pemesanan untuk Strategi Penawaran dan Pemasaran Produk Dengan Pendekatan Metode PrefixSpan - Puspita Nurul Sabrina (Annual Research Seminar (ARS), 2016)
A business goes well depends on the sales of the business products and demanding for product called orders. The efforts to obtain orders is an essential process in the business, one of process is giving proper attention in the form of follow-up and offers to consumers. The large number of consumers sometimes will make difficult to set goals and follow-up deals. To get targeted and effective marketing deals could be by understanding the sequence patterns of customer orders. However, it is difficult to get the patterns in the usual reports or format. There is some method to get the ordered pattern called sequential pattern mining. In this research, tried to use PrefixSpan methods to process sequential pattern mining. This method is still relevant implemented on the order/sales report/data by using the order date and associated with the name of consumers who make order. Order/sales data is prepared and transformed in a format that becomes the input of PrefixSpan method called sequences and thn processed by machine of PrefixSpan. Testing result showed consumer order patterns containing connectedness among consumers to the others customer in ordering product. Patterns that obtained can be used as a reference to get more effective marketing strategy in a company